2003
DOI: 10.1080/10402000308982608
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Misalignment on the Performance of Flexible Porous Journal Bearings

Abstract: A n~athematical model is introduced to study the effects of journal misalignment on the hydrodynamic lubrication performance offitlire flexible porous journal bearings. A modified form of Reynolds equation, which was derived from the Brinkman-extended Darcy equations and Stokes' equations, is utilized in the present study. The journal misalignment is allowed to vary in magnitude as well as in direction with respect to the bearing boundaries.The predicted pe~ormance characteristics of porous journal bearings ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
3
9
0
Order By: Relevance
“…From the figure, it is noted that the positions of the two pressure peaks are on the either side of the mid-plane and they are axially near both ends of the bearing. Similar observation is reported by Elsharkawy 21 for misaligned flexible single-layer porous bearings.…”
Section: Discussion Of Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…From the figure, it is noted that the positions of the two pressure peaks are on the either side of the mid-plane and they are axially near both ends of the bearing. Similar observation is reported by Elsharkawy 21 for misaligned flexible single-layer porous bearings.…”
Section: Discussion Of Resultssupporting
confidence: 89%
“…But these investigations are restricted in plain journal bearings. Elsharkawy 21 showed that under high permeability, the misalignment effect on the performance of porous journal bearing can be neglected. Limited literature are available on the performance of a misaligned double-layered porous bearing under coupled-stress lubrication.…”
Section: Introductionmentioning
confidence: 99%
“…Elsharkawy [123] in 2003 investigated the effect of journal misalignment on the performance of flexible porous journal bearings. They showed that the effect of misalignment in porous journal bearings can be neglected when the permeability is high.…”
Section: Porosity Effectsmentioning
confidence: 99%
“…The iterative numerical scheme presented in Elsharkawy [20] is used to solve the mathematical model, which consists of the modified Reynolds equation and the film thickness equation. In this scheme, Elrod's [21] cavitation algorithm, which satisfied the conservation of mass flow across the rupture and reformation boundaries, was implemented in the numerical scheme to predict the cavitation boundary more accurately than the conventional analysis, which uses the Reynolds condition.…”
Section: Mathematical Modelmentioning
confidence: 99%